Transfigurasi Semantik Kata Ha almah Menjadi Parthenos: Sebuah Ulasan Yesaya 7:14 dan Matius 1:23 - Saputra, Gilbeth Pramana (Views : Jurnal Teologi dan Biblika, 2024)
Abstract: Matthew's citation of Isaiah 7:14 is one of the thorny issues in biblical studies. The problem is when Matthew interprets the word almah into parthenos to be attributed to Mary. The Opponents argue that Matthew has deliberately changed the word almah in Isaiah 7:14 so that the original meaning of the verse has been corrupted. For the cons, almah cannot mean virgin. The author uses a semantic approach and textual analysis to understand the conversion of almah into parthenos. Through this article. The author concludes that Matthew's interpretation of almah to parthenos is correct. Matthew did not corrupt the original meaning of Isaiah 7:14. There are 2 arguments from the author. First, almah can be interpreted as parthenos or virgin because the two terms in the Old Testament are interchangeable. The criteria that describe almah is a woman who is not yet married or married but has never had sexual intercourse with man. This criterion is suitable for Mary. Secondly, Isaiah 7:14 which retains the word parthenos has been around for a long time, 200 years before Jesus was born. So, Matthew's use of the word parthenos is pure without damaging the original text. Isaiah 7:14 text because the content of Matthew 1:23 is very similar to the Septuagint version of Isaiah 7:14.